2021
DOI: 10.1186/s12864-020-07319-x
|View full text |Cite
|
Sign up to set email alerts
|

A review of deep learning applications for genomic selection

Abstract: Background Several conventional genomic Bayesian (or no Bayesian) prediction methods have been proposed including the standard additive genetic effect model for which the variance components are estimated with mixed model equations. In recent years, deep learning (DL) methods have been considered in the context of genomic prediction. The DL methods are nonparametric models providing flexibility to adapt to complicated associations between data and output with the ability to adapt to very comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 96 publications
0
118
0
2
Order By: Relevance
“…We performed a random grid search of hyperparameters using the h2o.grid function in the h2o R package (https://cran.r-project.org/web/packages/h2o, accessed on 7 May 2021) in order to select the optimal hyperparameters combination that minimizes the predictive loss function (i.e., prediction error) of the model for each trait (Figure 2). The random grid search was performed using the training set from each CV design (10-fold_HO, BS_HO, BS+HO_10fold, Multi-breed and Multi-breed CV2) for each trait, splitting it into a 5-fold CV [22]. Thus, 4 folds were assigned to hyperparameter optimization, aiming to find the best combination of the main hyperparameters for GBM approach, while the 1 remaining fold was used to evaluate the model performance based on the loss function (root mean square error-RMSE) and prediction accuracy (r-square-r 2 ) [19].…”
Section: Methodsmentioning
confidence: 99%
“…We performed a random grid search of hyperparameters using the h2o.grid function in the h2o R package (https://cran.r-project.org/web/packages/h2o, accessed on 7 May 2021) in order to select the optimal hyperparameters combination that minimizes the predictive loss function (i.e., prediction error) of the model for each trait (Figure 2). The random grid search was performed using the training set from each CV design (10-fold_HO, BS_HO, BS+HO_10fold, Multi-breed and Multi-breed CV2) for each trait, splitting it into a 5-fold CV [22]. Thus, 4 folds were assigned to hyperparameter optimization, aiming to find the best combination of the main hyperparameters for GBM approach, while the 1 remaining fold was used to evaluate the model performance based on the loss function (root mean square error-RMSE) and prediction accuracy (r-square-r 2 ) [19].…”
Section: Methodsmentioning
confidence: 99%
“…Deep learning-based neural network studies demonstrated that accuracies must be increased by pre-trained models and data augmentation (Castro et al, 2020). Nevertheless, deep learning progress is accelerating and will be able to perform better predictions than ever (Montesinos-López et al, 2021). Although it has been the subject of debate in the past, extra investment in phenotyping technologies is becoming more accepted to capitalize on recent developments in crop genomics and prediction models.…”
Section: Additional Methods Applied To Tfg Breedingmentioning
confidence: 99%
“…In short, ML [138,[176][177][178][179] and deep learning approaches [133,170,180,181] promise assisting the conservation [102,[182][183][184], managing [185,186], prioritization [187][188][189], and introgression [190,191] of crop wild variation from genebanks (Figure 2). ML may be particularly useful in unexplored isolated pockets of diversity, which contain allelic variants otherwise eroded from modern genotypes [192,193].…”
Section: Geavs Geavsmentioning
confidence: 99%